The Figure of Speech Analysis of Jane Austen Novel "Pride and Prejudice" - Yoga Prihatin (Cakrawala: Jurnal Pendidikan, 2010)
This study investigates the figures of speech used in JaneAusten‟s novel „Pride and Prejudice and the messages implied on them.The subject is Jane Austen‟s novel „Pride and Prejudice.‟ The data werecollected through several steps; reading, translating, and grouping. Theresults show that there are five figures of speech namely; Metaphor,Hyperbole, Irony, Sarcasm, and Personification found in Jane Austen‟snovel „Pride and Prejudice.‟